KONSEP MAQĀṢID ASY-SYARĪ’AH, KRITIK ATAS NALAR LIBERALIS - Sofyan Sulaiman (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The discussion of the maqāṣid syari'ah is so prominent in the discussion of Islamic law. This is due to the response of Muslim scholars to the current social reality of the ummah. At least there are two opposing camps, first, the revivalists (mujaddid) who want the Shari'a are carried out according to what they are ordered to get mashlahah, while the second group, liberals, only want the substance to be carried out by ignoring the sharia text. This article is in response to the views of Muslim scholars, how the real maqashid concept is in Islam